Acceptance testing of integrated picture archiving and communications systems...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Lewis TE; Horton MC; Kinsey TV; Shelton PD (Journal of Digital Imaging)
An integrated picture archiving and communication system (PACS) is a large investment in both money and resources. With all of the components and systems contained in the PACS, a methodical set of protocols and procedures must be developed to test all aspects of the PACS within the short time allocated for contract compliance. For the Department of Defense (DoD), acceptance testing (AT) sets the protocols and procedures. Broken down into modules and test procedures that group like components and systems, the AT protocol maximizes the efficiency and thoroughness of testing all aspects of an integrated PACS. A standardized and methodical protocol reduces the probability of functionality or performance limitations being overlooked. The AT protocol allows complete PACS testing within the 30 days allocated by the digital imaging network (DIN)-PACS contract. AT shortcomings identified during the testing phase properly allows for resolution before complete acceptance of the system. This presentation will describe the evolution of the process, the components of the DoD AT protocol, the benefits of the AT process, and its significance to the successful implementation of a PACS. This is a US government work. There are no restrictions on its use.